Actual minds, possible worlds - Bruner, Jerome S. (Jerome Seymour) (Jerusalem-Harvard lectures., 1986)
Drawing on recent work in literary theory, linguistics, and symbolic anthropology, as well as cognitive and developmental psychology Professor Bruner examines the mental acts that enter into the imaginative creation of possible worlds, and he shows how the activity of imaginary world making undergirds human science, literature, and philosophy, as well as everyday thinking, and even our sense of self. - Publisher.